Review of Anti-Inflammatory Herbal Medicines - Mona Ghasemian; Sina Owlia; Mohammad Bagher Owlia (Advances in Pharmacological Sciences)
Medicinal plants and their secondary metabolites are progressively used in the treatment of diseases as a complementary medicine. Inflammation is a pathologic condition that includes a wide range of diseases such as rheumatic and immune-mediated conditions, diabetes, cardiovascular accident, and etcetera. We introduce some herbs which their anti-inflammatory effects have been evaluated in clinical and experimental studies. Curcuma longa, Zingiber officinale, Rosmarinus officinalis, Borago officinalis, evening primrose, and Devil’s claw are some of the introduced medicinal herbs in this review. Since the treatment of inflammation is not a one-dimensional remedy, this review tries to reach a multidimensional therapeutic approach to inflammation with the help of herbal medicine and modification in lifestyle.